PERANCANGAN TEMPAT HIBURAN CAMPURAN PADA KAWASAN TANAH ABANG TIMUR - Ronald Emillio; Budi Adelar Sukada (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2022)
Urban acupuncture is a method to restore degraded urban areas, through identification of urban system problems. If problems are successfully identified, then design interventions can be made. Tanamur is a discotheque that operated from 1970 to 2005. Tanamur stands for Tanah Abang Timur, which is also the name of the area where the Tanamur building is located. The purpose of this study, among others, is to identify the success factors of the Tanamur discotheque, as well as to examine discotheque buildings in general, to find urban acupuncture solutions that can be applied to restore the iconic function of the Tanamur area as a place of entertainment. The methodology used is content analysis. The findings of this study are then used to form design concepts and architectural programs. Through the studies that have been carried out, the architectural design solution to carry out urban acupuncture in the Tanamur area is to create an attractor in the form of a building for various entertainment functions, as a place of recreation for residents and immigrants who stop by the Tanah Abang Timur area. Keywords:  Architecture; Discotheque; Urban acupuncture; Tanamur Abstrak Urban acupuncture merupakan suatu metode untuk memulihkan area urban yang mengalami degradasi, melalui identifikasi permasalahan sistem urban. Apabila permasalahan ditemukan, maka dilanjutkan dengan intervensi desain. Tanamur merupakan sebuah diskotek yang beroperasi dari tahun 1970 hingga 2005. Tanamur merupakan singkatan dari Tanah Abang Timur, yang juga merupakan nama dari kawasan tempat bangunan Tanamur berada. Tujuan dari kajian ini antara lain adalah untuk mengidentifikasi faktor kesuksesan diskotek Tanamur, serta mengkaji bangunan diskotek secara umum, untuk menemukan solusi urban acupuncture yang dapat diterapkan untuk mengembalikan fungsi ikonik kawasan Tanamur sebagai tempat hiburan. Metodologi yang digunakan adalah analisis isi. Kemudian temuan dimanfaatkan untuk membentuk konsep desain dan program arsitektur. Melalui kajian yang telah dilakukan, solusi desain arsitektur untuk melakukan urban acupuncture pada kawasan Tanamur adalah dengan menciptakan atraktor kawasan berupa bangunan untuk beragam fungsi hiburan, sebagai tempat rekreasi untuk penghuni maupun pendatang yang singgah ke kawasan Tanah Abang Timur.